Pemberdayaan Masyarakat Melalui Badan Usaha Milik Desa (BUMDes) “Pelemwatu Mandiri” di Kabupaten Gresik - Soeliyono, Firda Fitri; Hardjati, Susi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Community empowerment is a process aimed at enhancing the capacity of individuals and groups to achieve independence, productivity, and competitiveness, both economically and socially. One concrete form of community empowerment at the village level is through the establishment of Village-Owned Enterprises (BUMDes) as economic institutions based on local potential. BUMDes not only function as profit-oriented enterprises but also serve as platforms to encourage community participation in village development. This study aims to describe and analyze the process of community empowerment through BUMDes “Pelemwatu Mandiri” in Pelemwatu Village, Menganti Subdistrict, Gresik Regency. The research uses a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The data analysis follows four stages: data collection, data condensation, data presentation, and conclusion drawing. The analysis focuses on four key aspects of empowerment: human development, business development, environmental management, and institutional strengthening. The findings show that BUMDes “Pelemwatu Mandiri” plays an active role in empowering the community through these four aspects and has successfully increased local capacity. Although some obstacles remain, such as low public interest in training programs and limited understanding of technology, in general, BUMDes “Pelemwatu Mandiri” has succeeded in promoting independence and developing the local potential of the village community.